Adipose-Derived Stem Cells for Future Regenerative System Medicine - Yani Lina (Indonesian Biomedical Journal, 2012)
BACKGROUND: The potential use of stem cell-based therapies for repair and regeneration of various tissues and organs offers a paradigm shift that may provide alternative therapeutic solutions for a number of disease. Despite the advances, the availability of stem cells remaining a challenge for both scientist and clinicians in pursuing regenerative medicine. CONTENT: Subcutaneous human adipose tissue is an abundant and accessible cell source for applications in tissue engineering and regenerative medicine. Routinely, the adipose issue is digested with collagenase or related lytic enzymes to release a heterogeneous population for stromal vascular fraction (SVF) cells. The SVF cells can be used directly or can be cultured in plastic ware for selection and expansion of an adherent population known as adipose-derived stromal/stem cells (ASCs). Their potential in the ability to differentiate into adipogenic, osteogenic, chondrogenic and other mesenchymal lineages, as well in their other clinically useful properties, includes stimulation of angiogenesis and suppression of inflammation. SUMMARY: Adipose tissue is now recognized as an accessible, abundant and reliable site for the isolation of adult stem cels suitable for the application of tissue engineering and regenerative medicine applications. The past decade has witnessed an explosion of preclinical data relating to the isolation, characterization, cryopreservation, differentiation, and transplantation of freshly isolated stromal vascular fraction cells and adherent, culture-expanded, adipose-derived stromal/stem cells in vitro and in animal models. KEYWORDS: adipose tissue, adult stem cells, regenerative medicine, mesenchymal stem cells.